Time-resolved transcriptomic and proteomic profiling of Heyndrickxia coagulans during NaOH-buffered L-lactic acid production - Huang, Xing; Tian, Wenzhe; Wang, Xiuwen; Qin, Jiayang (Frontiers in Microbiology, 2023)
The L-lactic acid (L-LA) fermentation process, based on sodium hydroxide neutralization, demonstrates environmental friendliness during product extraction. However, lactate fermentation is hindered by the pronounced stress effect of sodium lactate on the strain compared with calcium lactate. In this study, we performed time-resolved transcriptomic and proteomic analyses of Heyndrickxia coagulans DSM1 during NaOH-buffered L-LA production. The expression levels of the glycolytic genes demonstrated an initial increase followed by a subsequent decrease, whereas the tricarboxylic acid cycle genes exhibited an initial decrease followed by a subsequent increase throughout the fermentation process. Moreover, we identified clusters of genes consisting of transcription factors and ATP-binding cassette (ABC) transporters that demonstrate a progressive elevation of expression levels throughout the fermentation process, with significant upregulation observed at later stages. This investigation yields valuable insights into the response mechanisms of H. coagulans during NaOH-buffered L-LA fermentation and presents potential targets for metabolic engineering.